CREATION OF AN EFFECTIVE MARKETING INFORMATION SYSTEM TO SUPPORT THE TOURISM SECTOR IN OUR COUNTRY - Suyunova Kamilla Bakhromovna (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In order to choose and develop a strategy for the development of tourist enterprises and organizations, managers in the management process need information related to their search, processing and analysis. Usually, these processes are carried out at great expense. This causes an increase in the cost of tourist services and, therefore, has a negative impact on its competitiveness in the world market. The article describes the creation and implementation of mechanisms for effective use of these costs.